Materiality and Meaning in Literary Studies (Schriften zur Kultur- und Mediensemiotik | Online, 2016)
Recently, non- and paraverbal properties of literary texts at the level of documentary inscription (i.e. materiality), seen individually or as aspects of a so-called "material text", that is, the union of materiality and verbal sign systems, received an increasing amount of attention in textual scholarship and literary studies. Here, "meaning" or at least "semantic potentiality" has been attributed to both or either and physical features of texts have been construed as hitherto neglected aspects of literary communication and literary aesthetics. In what follows, I will present a brief conspectus of the current debate and then try to provide a reconstruction of underlying ideas by answering the question "now does a material text mean?". Taking a descriptive meta-perspective and focusing on conceptual and methodological clarification, I try to clarify the somewhat blurry expressions "meaning", "to mean" and the like by translating them into the distinct terminology of semiotics and transferring them into the theoretical framework of an instrumentalist notion of signs.